Graphite‐schist blocks in the Franciscan Mélange, San Simeon, California: Evidence of high‐P metamorphism. (17th February 2016) - Ukar, E.; Cloos, M.
Abstract: The seacliff exposure at San Simeon, California, contains graphite‐schist blocks in a shale‐matrix, an undocumented lithology within the Franciscan mélange. Thirty graphite‐schist blocks were studied to discover all the varieties in this classic locality of mélange. Based on their mineralogical assemblage and composition, and textural characteristics the graphite‐schists in San Simeon are subdivided into two main types (Type I and II) with two subdivisions each (A and B). Type IA and IIA blocks are the most abundant. Type IA graphite‐schists are siltstone/fine greywacke‐like, preserve sedimentary textures, and lack lawsonite. Type IB graphite‐schists are mineralogical and texturally similar to Type IA schists, but are finer grained siltstone and shale. Type IIA graphite‐schists are compositionally layered and contain quartz‐ and albite‐rich layers and dark graphite‐ and intergrown mica/chlorite‐rich layers. Nine out of the 15 Type IIA blocks contain lawsonite. Two Type IIA blocks also contain aragonite (+calcite) in veins. Type IIB graphite‐schists are mostly composed of quartz and minor graphite, intergrown chlorite and white mica, and white mica pseudomorphs after lawsonite. The phengite content of mica in Type IIA blocks is higher than that of mica in Type IA graphite‐schists, confirming they were metamorphosed under high‐ P /low‐ T conditions. Type IA blocks were recrystallized between 200 and 250 °C at < 3 kbar; whereas, Type IIA blocks were metamorphosed under higher pressure conditions, probably at 250–300 °C and 3–5 kbar. Most likely both types of graphite‐schists were derived from a similar layered siltstone/fine greywacke/shale protolith. Organic matter‐rich sediments deposited in the trench axis were subducted along with oceanic crust during Franciscan subduction. Type I graphite‐schists were subducted to depths <10 km, whereas Type II graphite‐schists were subducted to depths 15 km where they were underplated under high‐ P conditions. The graphitic metasedimentary rocks were juxtaposed with mafic lithologies from the subducted oceanic crust that were metamorphosed to blueschist facies and retrograded to greenstone as they returned to the surface in the subduction channel shear zone.